Risk Assessment, Risk Management, and Risk Communication at Drug Industries PT. Kimia Farma (Persero) Tbk. Plant Bandung - Suherdin1, Noeroel Widajati1, Ratna Dian Kurniawati2, Abdul Rohim Tualeka1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
There have been many accidents and occupational diseases caused by weak risk management efforts. Risk management can be carried out by starting with a risk assessment. Risk assessment is an important aspect of occupational health and safety. The pharmaceutical industry has a high risk of occupational health and safety. This study aims to identify the level of occupational health and safety risks and provide control recommendations. This research is descriptively using the Job Safety Analysis (JSA) method. The results of the identification show that from 19 work steps 10 of which include high risk, 8 including moderate risk and 1 low risk. The hazards identified include chemical, physical, ergonomic and fire hazards. High risks include hazards originating from chemicals as raw materials for making drugs. Several control measures have been taken, but to ensure worker health and safety, additional efforts should be made such as noise suppression personal protective equipment, special masks for use in chemical hazards and work accident emergency response procedures. Risk communication at the drug company is going well.